Seroprevalence and molecular characterization of lumpy skin disease virus in Bahawalpur district of South Punjab, Pakistan - Nadeem, A; Nasir, A.; Rehman, A.U.; Kashif, M.; Rahman, A.U.; Hussain, A.; Sarwar, M.; Saeed, M.A.; Reichel, M.P.; Gonzalez, J.P. (Polish Journal of Veterinary Sciences, 2025)
Lumpy skin disease (LSD) is a viral infectious disease that affects cattle and causes significant economic losses, particularly in low and medium income countries, where livestock is often the main source of income for small-scale farmers and rural communities. In the last few years, the disease has become widespread in several countries in Asia, including Pakistan. The present cross-sectional study aimed to determine the seroprevalence and molecular characteristics of LSD virus (LSDV) among cattle in the Bahawalpur district (Pakistan), while identifying potential associated risk factors. A total of 400 serum samples were collected from cattle and analysed using a commercial ELISA kit to determine seroprevalence. Additionally, 12 skin scrapping samples of cattle were collected from sick animals to detect and characterize the currently potentially circulating LSDV strains using PCR, targeting the P32 gene. The overall LSD seroprevalence among cattle was found to be 38.0%, with significant variation observed between different geographical areas of the Bahawalpur district, showing the highest prevalence of 46.2% in Yazman Tehsil. Age and feeding system were identified as significant risk factors for LSD occurrence in cattle. The genetic analysis revealed a high genomic similarity between the LSDV strain sequences reported in Asian and Middle Eastern countries. The P32 gene phylogenetic analysis further confirmed the close relationship between LSDV sequences from Pakistan and vaccine strains of sheep and goat pox viruses. The present study provides important baseline information for an understanding of the epidemiology and characterisation of LSDV enzootic strains in Pakistan, and highlights the need for effective disease control strategies, including vaccination campaigns, particularly in disease-endemic regions.
Keywords: cattle; lumpy skin disease; molecular characterization; p32 gene; phylogeneticanalysis; seroprevalence